2016
DOI: 10.1111/imr.12423
|View full text |Cite
|
Sign up to set email alerts
|

MHC class I‐related molecule, MR1, and mucosal‐associated invariant T cells

Abstract: The MHC-related 1, MR1, molecule presents a new class of microbial antigens (derivatives of the riboflavin [Vitamin B2] biosynthesis pathway) to mucosal-associated invariant T (MAIT) cells. This raises many questions regarding antigens loading and intracellular trafficking of the MR1/ligand complexes. The MR1/MAIT field is also important because MAIT cells are very abundant in humans and their frequency is modified in many infectious and non-infectious diseases. Both MR1 and the invariant TCRα chain expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
120
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(125 citation statements)
references
References 125 publications
(382 reference statements)
3
120
0
2
Order By: Relevance
“…MAIT cells play a role in the host defense against bacterial infections 7, 8 . Their semi-invariant Vα7.2-Jα33 T cell receptor recognizes vitamin B metabolites from bacteria such as E. coli presented on major histocompatibility complex class I-related molecules (MR1) 912 . A recent study demonstrated that MAIT cells localize around bile ducts in the portal tracts of the liver and respond to bacterial antigens 13 .…”
Section: Introductionmentioning
confidence: 99%
“…MAIT cells play a role in the host defense against bacterial infections 7, 8 . Their semi-invariant Vα7.2-Jα33 T cell receptor recognizes vitamin B metabolites from bacteria such as E. coli presented on major histocompatibility complex class I-related molecules (MR1) 912 . A recent study demonstrated that MAIT cells localize around bile ducts in the portal tracts of the liver and respond to bacterial antigens 13 .…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that anti-TNF therapy, a well established anti-inflammatory therapy in AS, results in systemic and intestinal reduction of ILC3 and in strong reduction of intestinal expression of MAdCAM1 [37]. Mucosal-associated invariant T (MAIT) cellsda novel innate-like T-cell population, recognizing a highly conserved antigen derived from the microbial riboflavin synthesis pathway [40]dhave been recently implicated in the pathogenesis of AS. Gracey E et al [41] recently demonstrated that MAIT cells are reduced in frequency in the blood of patients with AS compared with HCs.…”
Section: Immune Alterations In the Gut Of Spa Patientsmentioning
confidence: 99%
“…MAIT cells are a recently identified subset of innate-like T cells with a conserved invariant T cell antigen receptor (TCR) α-chain, composed of Vα7.2-Jα33 in humans and Vα19-Jα33 in mice, and express high levels of the C-type lectin receptor CD161 or the interleukin (IL)-18 receptor α subunit 6. MAIT cells are initially called ‘mucosal-associated’ because of relative abundance of the Vα7.2-Jα33 transcript detected in human gut biopsies and the enrichment of homologous Vα19-Jα33 transcript among murine lamina propria lymphocytes compared with intraepithelial lymphocytes or mesenteric lymph nodes 7.…”
mentioning
confidence: 99%
“…One major function of MAIT cells is to inhibit bacterial infection through the invariant TCR that recognises microbial riboflavin/vitamin B2 metabolites presented by the major histocompatibility complex class I-related protein 1 6. MAIT cells can be also activated by inflammatory cytokines such as IL-12 and IL-18 in a TCR-independent manner, and subsequently produce a variety of cytokines such as tumour necrosis factor-alpha, interferon gamma, IL-17 and IL-22, suggesting that in addition to their antibacterial functions, MAIT cells may play a role in modulating immune responses in various types of liver diseases 6.…”
mentioning
confidence: 99%
See 1 more Smart Citation